The Influence of Work Motivation and Organizational Culture on the Performance of Margasari District Health Center Employees Through Organizational Commitment as a Mediating Variable: The Influence of Work Motivation and Organizational Culture on the Performance of Margasari District Health Center Employees Through Organizational Commitment as a Mediating Variable - dana, Ahmad Muslih Ramadhana; Mukhroji Mukhroji (Jurnal of Management and Social Sciences, 2026)
The Influence of Work Motivation and Organizational Culture on the Performance of Margasari District Health Center Employees Through Organizational Commitment as a Mediating Variable